2016
DOI: 10.1016/j.cub.2015.12.068
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Kinesin UNC-104/KIF1A Is a Key Regulator of Synaptic Aging and Insulin Signaling-Regulated Memory

Abstract: Summary Aging is the greatest risk factor for a number of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease. Furthermore, normal aging is associated with a decline in sensory, motor, and cognitive functions. Emerging evidence suggests that synapse alterations, rather than neuronal cell death, are the causes of neuronal dysfunctions in normal aging, and in early stages of neurodegenerative diseases. However, little is known about the mechanisms underlying age-related synaptic decline. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…The loss of intrinsic regenerative ability in aging adult neurons is not merely a secondary consequence of a decrepit animal, but is a regulated process occurring specifically in neurons (Byrne et al, 2014). Thus, adult decline of axon regeneration is an early effect of neuronal aging, occurring before other effects such as aberrant axon branching, defects in synaptic transmission, and decreased kinesin function (Pan et al, 2011; Tank et al, 2011; Toth et al, 2012; Liu et al, 2013; Li et al, 2016). …”
Section: Age Vs Axon Regenerationmentioning
confidence: 99%
“…The loss of intrinsic regenerative ability in aging adult neurons is not merely a secondary consequence of a decrepit animal, but is a regulated process occurring specifically in neurons (Byrne et al, 2014). Thus, adult decline of axon regeneration is an early effect of neuronal aging, occurring before other effects such as aberrant axon branching, defects in synaptic transmission, and decreased kinesin function (Pan et al, 2011; Tank et al, 2011; Toth et al, 2012; Liu et al, 2013; Li et al, 2016). …”
Section: Age Vs Axon Regenerationmentioning
confidence: 99%
“…Maintaining CREB activity may be a way to preserve cognitive function with age in higher organisms, because CREB levels correlate with cognitive performance in mammals [31, 80, 109, 169], but the exact location and levels of this CREB maintenance will be important to avoid deleterious effects. Loss of short-term memory with age is less studied than long term memory, but several IIS targets have been identified that are required for normal STAM performance [97], and IIS mutants maintain STAM performance with age due to preserved pre-synaptic function [117]. Future work in model systems, both vertebrate and invertebrate, will be invaluable in the study of these targets in age-related cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, daf-2’s enhanced STAM memory performance with age was discovered to also be due to maintenance of synaptic integrity [117]. The anterograde kinesin motor UNC-104/KIF1A regulates synapse distribution, synaptic transmission, and motility with age in C. elegans [117].…”
Section: Intersection Of Longevity Pathways and Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…What processes might axonal pufs regulate? We previously found that molecules that regulate pre-synaptic transport and transmission are important for learning and associative memory formation (Arey et al, 2018;Kaletsky et al, 2016;Lakhina et al, 2015;Li et al, 2016). Furthermore, pumilio is an important regulator of long-term memory in Drosophila (Dubnau et al, 2003), and mammalian PUM1/2 regulate dendrite morphogenesis, synaptic function, neuronal excitability, and hippocampal neurogenesis (Siemen et al, 2011;Vessey et al, 2010;Zhang et al, 2017).…”
Section: Elegans Pufs Are Both Necessary Memory Components and Memmentioning
confidence: 99%